Resim Çözümlemesi Üzerine: Jean Fouquet (1420-1481)’xxnin Melun Diptiğinde ”Güzel Kadın” Agnes Sorel - Üstünipek, Mehmet (My University, 2015)
On beşinci yüzyılın ortalarında Fransız saray ressamı Jean Fouquet tarafından saray hazinedarı Étienne Chevalier’nin siparişiyle yapılan Melun Diptiği, toplumsal ve tarihsel özellikleri, sanatçısı ve eserin malzeme- teknik, biçem, konu olarak incelenmesiyle ele alınmıştır. Resmin renkleriyle ortaya çıkan sembolizmi, Fransa’nın ulusal uyanışının bir yansımasıdır. Aynı zamanda resimde yer alan veya onlarla bağlantılı olan tarihsel kişiler, resmin dinsel içeriğinin ardındaki dünyevi niteliği ortaya çıkarmaktadırlar. Ulusal tarih ötesinde kişisel tarihlerin de bir resmin ilk bakışta gizli duran özünün tanımlanabilmesindeki önemi vurgulamak açısından Melun Diptiği örnek bir çözümleme olanağı sağlamaktadır.

Commissioned by court treasurer Étienne Chevalier Melun Dyptich was painted by French court painter Jean Fouquet. In this paper this painting was analyzed through its social- historical context. Determining the place and importance of the artist in Renaissance French art also the medium, technique, style and subject matter of the work have been analyzed. The symbolism emerged by its colors is a reflection of national awakening of France. On the other hand the historical figures in the painting or others connected to them define the secular context of the painting behind the religious one. To underline the importance of the history in the terms of individuals not only national, Melun Dyptich is an ideal example for analyzing.
On Painting Analysis: “Beautiful Lady” Agnes Sorel in Jean Fouquet’s Melun Dyptich
Keywords: Melun Diptiği; Resim Çözümleme; Melun Dyptich; Painting Analyze; Jean Fouquet